Would Chinese Men Who Have Sex With Men Take Up Human Papillomavirus (HPV) Screening as an Alternative Prevention Strategy to HPV Vaccination? - Chan, Paul Shing-fong; Fang, Yuan; Chidgey, Andrew; Fong, Francois; Ip, Mary; Wang, Zixin (Frontiers in Medicine, 2022)
Background: Men who have sex with men (MSM) are at high risk for human papillomavirus (HPV) infection. A community-based organization (CBO)-private clinic service model promoting HPV vaccination among MSM was implemented in Hong Kong. The aim of this study was to evaluate the effectiveness of this service model in increasing HPV screening among MSM. Methods: This was a secondary analysis of the CBO-private clinic service model in increasing HPV screening among MSM. Participants were Hong Kong Chinese-speaking MSM aged 18-45 years who had never received HPV vaccination. All participants completed a telephone survey at baseline before receiving online intervention promoting HPV vaccination and completed another telephone survey 12 months afterward. Results: A total of 350 participants completed a baseline telephone survey and received interventions promoting HPV vaccination. Among 274 participants being followed up at Month 12, 33 (12.0%) received any type of HPV screening during the study period. Such uptake rate was similar to the prevalence of HPV screening in the past year measured at baseline (12.0% versus 9.9%, p=0.43). More MSM preferred HPV vaccination or HPV vaccination plus HPV screening, and very few preferred HPV screening alone. After adjusting for significant baseline characteristics, higher perceived susceptibility to HPV (adjusted odds ratio (AOR): 1.16, 95% confidence interval (CI): 1.00–1.34) and receiving HPV vaccination during the study period (AOR: 7.03, 95% CI: 3.07–16.13) were significantly associated with higher HPV screening uptake. Conclusions: The CBO-private clinic service model promoting HPV vaccination had limited impact in increasing HPV screening among MSM in Hong Kong. MSM in Hong Kong may not use HPV screening as an alternative prevention strategy to HPV vaccination. Future programs preventing HPV-related diseases among MSM in Hong Kong should focus on HPV vaccination promotion.